Efeito de dentifrícios fluoretados e suplementados com nanopartículas de trimetafosfato de sódio sobre a desmineralização, remineralização e erosão dentária - Danelon, Marcelle [UNESP] (2014)
The aim of this study was to evaluate the ability of conventional toothpaste (1100 ppm F) supplemented with micrometric or nano-sized sodium trimetaphosphate (TMP; TMPnano ), in reducing demineralization (in vitro), promote remineralization ( in situ ) and reduce erosion tooth (in vitro). In the study of demineralization of bovine enamel blocks (n = 96 ) selected by the initial surface hardness ( SHi ) were divided into eight groups of toothpaste (n = 12) without fluoride and without TMP (Placebo), 1100 ppm F (1100 ppm F) 1100 ppm F associated 1% TMP micrometric and nano-sized (1100 1%TMP; 1100 1%TMPnano), 1100 ppm F associated with 3% TMP micrometric and nano-sized (1100 3%TMP; 1100 3%TMPnano), 1110 ppm F associated with 6% TMP micrometric and nano-sized TMP (1100 6%TMP; 1100 6%TMPnano). The blocks were subjected to pH cycling for five days, and treatment with their toothpastes made 2x/day. Next, we determined the final surface hardness (SHf), integrated mineral loss (IML), differential integrated mineral loss (ΔIML) and fluoride (F) in the enamel. The results were subjected to analysis of variance followed by Student-Newman-Keuls test (p < 0.001). The group 1100 3 %TMPnano had the lowest mineral loss (SHF, IML and ΔIML) followed by 1100 3%TMP group (p < 0.001). The group 100 3%TMPnano showed a higher concentration of F in the enamel, followed by 1100 6%TMPnano (p < 0.001). For the study of remineralization of bovine enamel blocks (n = 192) were selected by the hardness of the surface after demineralization (SH1), and divided into four groups: Placebo, 1100 ppm F, 1100 3 % TMP micrometric (1100 TMP) and 1100 3% TMP nano-sized (1100 TMPnano ). Twelve volunteers wore palatal appliances with four blocks of demineralized enamel, for three days, and brushing held 3x/day. After the period of remineralization...